(untitled) (Journal of Social Sciences Review, 2025)
This study focuses on the mounting tensions in the Horn of Africa following a controversial deal in early 2024 between Ethiopian Prime Minister Abiy Ahmed and Somaliland President Muse Bihi Abdi. Under the agreement, Somaliland, a self-declared territory not internationally recognized, granted Ethiopia access to the Red Sea via Berbera Port for 5 decades. However, this moves enraged Somalia, which considers Somaliland an integral part of its sovereign territory. For landlocked Ethiopia, the accord offers vital maritime access, which will boost trade potential to Europe and beyond through the Red Sea and the Suez Canal. Ethiopia, in return, vowed a thorough assessment of Somaliland’s long-standing demand for international recognition, a move that could potentially trigger major geopolitical tension across the region. The research uses qualitative methodology, including a comprehensive review of literature, news reports, and academic sources, to analyze the deal’s background, motivations, and broader implicatio ns. The study concludes that, along with Somalia, many countries are opposing the agreement, mainly due to their own strategic or geopolitical interests in the region. Also, the U.S. may have a hidden agenda to turn Somaliland into another Taiwan, using it as a strategic foothold in the region, possibly seeking to create a Taiwan-China situation.